Accelerating Pre-stack Kirchhoff Time Migration by using SIMD Vector Instructions - Alves, Maicon; Drummond, Lúcia Maria; Pestana, Reynam (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2015)
The Pre-stack Kirchhoff Time Migration (PKTM) is a central process in petroleum exploration. As PKTM is computationally intensive, many works have proposed the use of accelerators like GPU and FPGA to improve its execution time. On the other hand, although many off-the-shelf processors are endowed with a set of SIMD vector instructions, few papers tackle the problem considering vectorization and, all of them, consider that compilers can successfully vectorize the code. In this paper, we show that a hand-written Kirchhoff code by using SIMD vector instructions is more efﬁcient than the autovectorized code provided by GCC. Experiments considering both real and synthetic datasets showed that our solution is up to eight times faster than the autovectorized one. We believe that the proposed strategy can be used together with the other ones to accelerate seismic migration methods in general without new investments in hardware and software.